2003
DOI: 10.2166/wst.2003.0224
|View full text |Cite
|
Sign up to set email alerts
|

High-rate anaerobic hydrolysis and acidogenesis of sewage sludge in a modified upflow reactor

Abstract: Continuous experiments were conducted to study the hydrolysis and acidogenesis of sewage sludge in an upflow reactor with an agitator and a gas-liquid-solid separator. Results of this study showed that 34-78% of volatile suspended solids (VSS) in sewage sludge was hydrolyzed at pH in the range 4.0-6.5, 35 degrees C and 4-24 hours of hydraulic retention time (HRT). About 31-65% of carbohydrate in sewage sludge, 20-45% of protein and 14-24% of lipid were acidified in this reactor. Hydrogen production was favored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 12 publications
1
22
0
2
Order By: Relevance
“…The suitable nutrients, expressed as C : N ratio, in fermentation substrates were therefore necessary for acidogenic bacteria to produce SCFAs efficiently. It was also reported that the accumulation of SCFAs during organic wastes acidification was affected by pH, but the relative information was obtained in the case of pH less than 7.0 [7,14]. It was observed in our study that pH was a key parameter which influenced the hydrolysis and acidification of fermentation substrate in the range of pH 4.0-11.0.…”
Section: Introductionmentioning
confidence: 49%
“…The suitable nutrients, expressed as C : N ratio, in fermentation substrates were therefore necessary for acidogenic bacteria to produce SCFAs efficiently. It was also reported that the accumulation of SCFAs during organic wastes acidification was affected by pH, but the relative information was obtained in the case of pH less than 7.0 [7,14]. It was observed in our study that pH was a key parameter which influenced the hydrolysis and acidification of fermentation substrate in the range of pH 4.0-11.0.…”
Section: Introductionmentioning
confidence: 49%
“…Total solids degradation was 41% of TVS. This is considered low compared to volatile solid destruction of 43.8-72.5% and 34-78% achieved by Elefsiniotis and Oldham (1994) and Yu et al (2003), respectively. These studies, however, used sewage sludge where biodegradability and surface area would be different from OFMSW used in our study.…”
Section: Lab-scale Batch Thermophilic Anaerobic Digestion Of Pre-aeramentioning
confidence: 75%
“…The experiments were carried out in 1000 mL conical flasks and the working volume was 500 mL. According to the reported results, 26,27 an acidic or near neutral pH condition is advantageous to VFAs production in the anaerobic digestion of sludge. Therefore, the initial pH of all samples was adjusted to 6.0 using 2 mol L −1 hydrochloric acid.…”
Section: Batch Fermentation Testsmentioning
confidence: 99%